Pengembangan E-Modul Berbasis Ethno-STEM pada Materi Geometri - Pramesti, Santika Lya Diah; Rini, Juwita; Ferdianto, Yogi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research is motivated by problems in the learning process. In this problem, it has an impact on the problem-solving ability of mathematics students at UIN K.H. Abdurrahman Wahid Pekalongan, therefore the development of e-module-based learning was made. This study aims to find out how to reconstruct the concept, validity and effectiveness of mathematics e-modules in local Javanese culture in ethno-STEM-based geometry learning. This research is R&D type with ADDIE development model. Which is proven to be valid and effective, the results of material and media validation tests reach 68% and 78% with valid cateogries.